Athletic Subculture within Student-Athlete Academic Centers - Rubin, Lisa M.; Moses, Ron A. (My University, 2017)
Over 400,000 student-athletes participate in NCAA intercollegiate athletics programs. Due to their dual roles as student and athlete, they have a different college experience than the general student population. Specialized academic centers and resources for student-athletes are part of the reason they are separated and often isolated from the rest of campus. Teams have their own unique academic subculture that influences each student-athlete in his or her academic pursuits. The purpose of this study is to explore the athletic academic subculture among student-athletes at the Division I level and the role the athletic academic center and special resources play in cultivating a separate culture from the campus culture. Symbolic interactionism was the framework used as the lens to view the results of this study in the context of neoliberalism.
Citation: Rubin, L. R., & Moses, R. A. (2017). Athletic Subculture within Student-Athlete Academic Centers. Sociology of Sport Journal. (Forthcoming). http://dx.doi.org/10.1123/ssj.2016-0138
Keywords: Athletics; Academic subculture; College; Neoliberalism